Spectral Studies and Bactericidal, Fungicidal, Insecticidal and Parasitological Activities of Organotin(IV) Complexes of Thio Schiff Bases Having no Donor Atoms - Nath, Mala (Hindawi Publishing Corporation, 1995)
Twelve new organotin(IV) complexes of the type RnSnLm [where n = 3, m = 1, R = CH(3) or C(6)H(5); n = 2, m = 2, R = C(6)H(5) or C(4)H(9) ; L = anion of Schiff bases derived from the condensation of 2-amino-5-(o-anisyl)-l,3,4-thiadiazole with salicylaldehyde (HL-1), 2- hydroxynaphthaldehyde (HL-2) and 2-hydroxyacetophenone (HL-3)] have been synthesized and characterized by elemental analysis, molar conductances, electronic, infrared, far-infrared, (1)H NMR and (119)Sn Mössbauer spectral studies. Thermal studies of two complexes, viz., Ph(3)Sn (L-1) and Ph(2)Sn(L-2)(2) have been carried out in the temperature range 25-1000∘C using TG, DTG and DTA techniques. All these complexes decompose gradually with the formation of SnO(2) as an end product. In vitro antimicrobial activity of the Schiff bases and their complexes has also been determined against Streptococcus faecalis, Klebsiella pneumoniae, Escherichia coli, Pseudomonas aeruginosa, Staphylococcus aureus Penicillin resistance (2500 units), Candida albicans, Cryptococcus neoformans, Sporotrichum schenckii, Trichophyton mentagrophytes and Aspergillus fumigatus. The Schiff bases (HL-1), (HL-2) and the organotin(IV) compounds have also been tested against various important herbicidal, fungicidal, insecticidal species and also for parasitological activity against freeliving nematode.